Estudo da viabilidade de sedimentos formulados para a aplicação em estudos ecotoxicológicos e químicos: ênfase para os interferentes endócrinos 17alfa-etinilestradiol e 17beta-estradiol - Arine, Ana Lúcia Fermino de Oliveira [UNESP] (2015)
The use of laboratory-formulated sediments have been widely adopted, and recommended by environmental protection organizations and other international agencies as USEPA, OECD, and ASTM, mainly for easy reproducibility by different laboratories, and for being free of unwanted contaminants and indigenous organisms. Aiming at the representation of tropical lotic environments, different sediment formulations were analyzed for use in toxicology studies of endocrine disruptors (EI), namely 17β-estradiol (E2) and 17α-ethinyl estradiol (EE2). Five different formulations were evaluated regarding dissolved oxygen, water hardness and pH over a period of 15 days, and on the adaptation of the benthic species Hyalella azteca regarding survival, growth, and reproduction parameters. The toxicity of E2 and EE2, both at the concentration of 30 ng/L, was observed in the nektonic organism Ceriodaphnia dubia, exposed to a solution extracted from spiked formulated sediment containing a minor amount of organic matter in a 8-days test. Survivability and reproduction parameters were evaluated using Kruskal-Wallis, t-test and bioequivalence t-test statistical methods. Chemical behavior of the compounds was analyzed regarding environmental degradation time in formulated sediment (after 2, 24, and 48 hours of contact), and sediment retention capacity after 2 hours of contact by quantification by gas chromatography-mass spectrometry (GC-MS). Results showed that the formulated sediments which contained smaller fractions of organic matter (1% and 3% dry weight) had better stabilization in relation to pH, and good acceptance by the species H. azteca. However, the formulated sediment environment was not ideal for C. dubia, which was therefore replaced by filtered interstitial water for E2 and EE2 tests. There was a statistically significant reduction in the number of newborns when exposed to control sediment and contaminants (Kruskal-Wallis, t-test, and bioequivalence ...